Proyecto de factibilidad para la instalación de un sistema de secado de arroz a través de paneles solares para la postcosecha en beneficio de los pequeños productores de arroz de la parroquia Juan Bautista Aguirre del cantón Daule - Flores Bajaña, Claudia Carolina (2016)
Rice is a gramineae and autogamous large plant, which requires the tropical climate in order to get the most favorable growth. It is known as semi-aquatic plant because it needs a medium surface water to sow the plant and their stems are highly branched which they can reach between 0.6 and 1.8 meters high. Most of the rice growing areas are located in the coast of Ecuador, but also it is growing in the Andes Mountains and the Amazons forest, but with little significant amounts……..